Evolution of kinematic transformation from the Altyn Tagh fault to the Qilian Shan in the northern Tibetan Plateau: from early Cenozoic initiation to mid-Miocene extrusion - Yang, Yizhou; Wang, Zhendong; Liu, Runchao; Peng, Luying; Zhang, Changhao; Guo, Zhaojie (Frontiers in Earth Science, 2023)
The Altyn Tagh fault has been a crucial tectonic boundary of the Tibetan Plateau during the Cenozoic India-Eurasia collision. However, issues have not been addressed regarding the Cenozoic evolution of the kinematic transformation from the eastern Altyn Tagh fault to the Qilian Shan. Here we focus on the kinematics at a crucial point, the Subei triple junction, along the Altyn Tagh fault, which was recorded by faulting in the Suganhu basin to the south of the junction. We reconstructed the structural pattern of faults and thickness distribution of the Cenozoic strata in the Suganhu basin by integrating seismic profiles, well logging, and topographic data. We inferred that only crustal shortening and thickening in the Danghenan Shan, a prominent topographic high, absorbed the strike-slip displacement along the Altyn Tagh fault during the early Cenozoic. Since the mid-Miocene, strike-slip fault belts within the Suganhu basin were initiated, based on the fault geometry and uneven thickness distribution across the fault belts. We thus proposed a mid-Miocene kinematic transformation realized by blocks extruding southeastward, as well as the crustal shortening and thickening in the entire Qilian Shan. Those blocks are bounded by preexisting weaknesses with lateral movements, and lithospheric heterogeneity played an essential role in the block-scale extrusion.